CO2 Frost Phenomenon for Binary System of Methane-Carbon Dioxide Mixtures - Gede Wibawa; Asalil Mustain; Sumarno Sumarno; Setiyo Gunawan (Institute for Research and Community Services, Institut Teknologi Bandung, 2015)
In the present study, the CO2 frost phenomenon of CH4-CO2 mixtures has been observed for the rational design of CO2 removal from natural gas using a controlled freeze out area. The CO2 frost conditions were estimated using the ZNE method and process simulation software (Aspen HYSYS® v7.3). The experiment was carried out using a double pipe heat exchanger (DPHE) with the concentration of CO2 in the gas mixture at 5 and 10% and pressure of the gas mixture from 1 to 20 bar. The equilibrium temperature predictions of the ZNE method and the process simulation software only had a slight difference, with a magnitude deviation of less than 1% for pressures below 20 bar and 3% for pressures in the range of 20-30 bar, respectively. In the experimental study, CO2 frost formation was detected at pressures of 1, 5, 10 and 20 bar. The locations of the initial CO2 frost formation were determined using a pressure drop indicator associated with the predicted frost temperatures obtained from the ZNE method and the process simulation software. For all studied variables, the locations of initial CO2 frost formation were found at 0.887-1.531 m from the inlet.